DESAIN DAN SIMULASI INTERIOR KABIN PENUMPANG PESAWAT BOEING 737-300 - Dwi Nugraheny; Eko Poerwanto; Tink Tonk Wicaksono (Compiler, 2015)
Not only an aircraft technology is growing , a visual display in the cabin of the aircraft was already developed according to the need. Currently aircraft interior design can change the perception of many people about it. The designers are increasingly creative in designing aircraft interiors amazing. Interior design visualization Boeing 737-300 passenger cabin aims to provide an overview better visualization and can facilitate to understanding of the scope of a space including economy -class passenger cabin Boeing 737-300 aircraft in the form of 3D design and simulation.